Accounting - Anthony, Robert N.
Accounting: Text & Cases, by Anthony, Hawkins, and Merchant covers both financial and managerial accounting as well as broader managerial issues. Chapters 1 -14 cover financial accounting, while Chapters 15-21 cover management accounting, and Chapters 22-28 focus on broader issues of control and corporate strategy. The approximately 120 cases that make up most of the end of chapter material are a combination of classic Harvard style cases and extended problems, with 10 completely new cases added to the 12th edition. Accounting: Text and Cases is a product of lifelong dedication to the discipline of accounting, and users of the book benefit from a breadth of experience that is sure to enrich your course and your students